NEO-INSTITUTIONAL APPROACH TO THE STUDY OF ELECTRONIC GOVERNMENT - Y. I. Vaslavskiy; S. V. Gabuev (Vestnik MGIMO-Universiteta)
The article is devoted to the neo-institutional approach as a methodological basis in the study of electronic government. In this article substantiates the choice of neo-institutional approach to the study of the processes of implementation of information and communication technologies in the activity of state institutions, analyzes the differences of neoinstitutionalism from traditional institutional approach, considers the features of the different directions of neo-institutionalism, namely sociological, historical and rational choice theory. Attention is paid to the reasons for the renewed interest in political institutions in political science. The article emphasizes the importance of considering the electronic government as an institution, and the conditions for its implementation in the Russian political system as the institutional environment. The authors pay special attention to the variety of sociological neo-institutionalism, used, in addition to political science in sociology of organizations. The article substantiates the value of using sociological institutionalism to explore the electronic government based on a comparative analysis of e-government projects in Russia and abroad and explores its heuristic capabilities. It examines the impact of the system of norms and values of the institutional environment on the processes of formation and development of electronic government in Russia. The research capacity of this theory is due to the fact that it allows us to trace the reasons for copying and replication of inefficient practices and organizational and management schemes, to identify the factors impeding innovation use by the state of electronic interaction technologies. It is emphasized that the use of the theory of institutional isomorphism is useful in the sphere of implementation of electronic technologies, in which a key role play pluralism, horizontal managerial communication, inter-agency coordination.